Optimalisasi Peran Organisasi IPNU IPPNU Dalam Menanamkan Karakter Religius Remaja - Khusnan, Ach; Syaifullah, M Arief (Program Studi Pendidikan Agama Islam, 2021)
In this era of globalization, there is a multidimensional crisis in all aspects of life in our society. The progress of science, technology and art is not matched by appropriate and quality culture and civilization, so that science and technology only gives birth to less civilized humans. This situation encourages educational institutions to have a responsibility to provide knowledge, skills and develop them both through formal and non-formal education. This study uses a descriptive qualitative approach with the type of case study research. The data collection methods in this study were observation, documentation and interviews. The data analysis used includes data reduction, data presentation and conclusion drawing. The results obtained are that the Nahdlatul Ulama Student Association organization, the Nahdlatul Ulama Women's Student Association (IPNU-IPPNU) is very important in instilling the religious character of teenagers in Pacuh Village, Balongpanggang District, Gresik Regency. because their activities are religious or religious. In addition, it is also the front line of NU regeneration and is one of the autonomous bodies in NU. Then members of IPNU-IPPNU are also pioneers of the younger generation in carrying out religious activities and as uswatun hasanah (good role models) for other students. IPNU-IPPNU is also a means to reduce the level of juvenile delinquency that often occurs in Pacuh Village.